Manajemen Pelatihan Mastering Islamic Finance di Pusdiklat Keuangan Umum - Fanny Amalina; Matin Matin; Amril Muhammad (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This research was conducted at the General Finance Training Center. Whichaims to identify training management Mastering Islamic Finance process. This researchwas done since october 2016 to january 2017. This research was using a qualitativeapproach with descriptive methods. Data collection is done through interview,observation and documentation study. Source of research data comes from keyinformants head of planning and development division, head of implementation division,and several informants supporters such as head of curriculum subdivision, currculumsubdivision and implementation subdivision staff.The results of this study indicate that: (1) Planning of Mastering Islamic FinanceTraining begins with training need analysis, preparing curriculum, materials, teachingmaterials, assign teachers, the requirements of the participants, the venue for training.Implementation of Mastering Islamic Finance Training at the general finance trainingcenter appropriate with the guidelines. (2) Implementation of the training activitiescarried out through several stages including methods independent study and face-to-face.The determination of participants Mastering Islamic Finance training based on therecommendation of General of Budget Financing and Risk Management